Evaluation of the Implementation of Total Quality Management on PT. Aksakindo Manufacturing - Rahmadiah Hanum (PT Inovasi Pratama Internasional, 2022)
this global era, only companies that are able to produce quality goods or services that meet customer demands can win the competition. Integrated quality management ( total quality management ) is a very appropriate strategy in an effort to company to achieve world class company performance performance ). PT. Aksakindo Manufacturing has implemented TQM, but products are still found imperfection or imperfection so it is necessary to do research Furthermore. The purpose of this study was to analyze the significance of Strategic construct influence (leadership, organizational culture, improvement sustainability, benchmarking, quality objectives and policies), analyze the significance of the effect of the Tactical construct (team development and solving problems, employee empowerment, engagement and training, use of information technology, supplier management) as well as analyzing the significance the influence of the Operational construct (goods and service design, process control, consumer orientation) to the construct of product quality produced by PT. Aksakindo Manufacturing . Determination of the sample using the purposive sampling method , namely sample selection with a specific goal or target. Based on analysis regression that has been done, it can be concluded: Construct Strategic, Tactical and Operational have a positive and significant impact on The quality of the resulting product. That is, the better the strategic construct, Tactical and Operational run by the company, the better the quality products produced by PT. Aksakindo Manufacturing .